Mightier than the sword [large type] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- Clifton chronicles, 2015)
In the aftermath of an IRA bombing, Harry uses his new literary station to raise awareness for his POW friend while Giles works to secure a political career and Sebastian's past threatens his engagement.